Resection of vaginal neoplasms by video-vaginoscopy in bitches - Silva, Marco Augusto Machado; Teixeira, Pedro Paulo Maia; Coutinho, Leandro Nassar; Gutierrez, Raquel Ribeiro; Macente, Beatrice Ingrid; Vicente, Wilter Ricardo Russiano; Toniollo, Gilson Hélio [UNESP]; Brun, Maurício Veloso (My University, 2014)
Background: Vaginal neoplasms usually represent a challenge for veterinary surgeons. Surgical resection often requires episiotomy or even laparotomy and pubic osteotomy, increasing the risk for intra and postoperative complications, such as severe pain, bleeding, wound infection or dehiscence and vaginal stenosis. Endoscopic treatment of neoplastic lesions is routinely used in human patients. However, the information about its use in small animals is sparse. Thus, the aim of the current study was to report two cases of successful vaginoscopic treatment of vaginal neoplasms in bitches. Case: A female Labrador weighing 26 kg (patient 1) and a mongrel bitch weighting 10 kg (patient 2) were attended due to vaginal bleeding. Physical examination revealed a pendunculated hard nodular mass in the caudal third of the vaginal dorsal floor in patient 1. In patient 2, two nodular, fibrous, infiltrated masses of different dimension were touched on the mucosa of the caudal third of the vagina. The vaginal cytology revealed erythrocytes, cellular debris and anestrus in both cases. Given the clinical suspicion of vaginal neoplasia, the endoscopic approach by vaginoscopy was chosen in order for diagnostic investigation and surgical treatment. Under general anesthesia, a rigid 10-mm telescope with 6-mm working channel was employed for initial examination. A 10-mmHg CO2 pneumovagina was estabilished using an automatic insufflator. A pedunculated spherical neoplastic mass of approximately 2 cm of diameter was excised from patient 1 using a simultaneous bipolar coagulation and cut forceps, inserted through the working channel of the telescope. In patient 2, the two infiltrated masses were resected using cup type biopsy forceps, followed by cauterization of the neoplastic underlining area with bipolar forceps, also through the working channel. The sampled specimen were sent for histopathological examination, which revealed leiomyosarcoma and fibroepithelial hyperplasia in patients 1 and 2, respectively. Moreover, no other therapy was prescribed and the patients convalesced uneventfully. Discussion: The surgical procedures lasted 23 and 38 min in patients 1 and 2, respectively. Patients recovered uneventfully in the early postoperative period, with no signs of pain. The operative-telescope proved to be versatile and effective for vaginoscopic resection of neoplasms, which was efficient for both diagnostic and therapeutic purposes. The patients presented excellent recovery with minimally invasive surgical trauma, especially compared with conventional techniques. The majority of tumors found in the vagina of dogs are benign, mostly from smooth muscle or fibrous tissue origin (leiomyoma, fibroma and leiomyosarcoma). Surgical excision of the tumor combined with ovariohysterectomy is usually effective to prevent recurrence. After 3 months, patient 1 was submitted to clinical and laboratory tests, including a second look vaginoscopy. Vaginal endoscopic examination revealed only small area of approximately 3 mm scar on the resection site, showing no evidence of recurrence and/or metastasis. Moreover, vaginoscopy was able to avoid the need for episiotomy or laparotomy for resection of the vaginal masses. In conclusion, the resection of vaginal neoplasia by video-vaginoscopy approach was feasible, effective and minimally invasive, which can be an alternative to conventional surgical approaches.
Keywords: Dogs; Endosurgery; Vaginal tumors; Vaginoscopy